The expression of estrogen, prolactin, and progesterone receptors in mammary gland and liver of female rats during pregnancy and early postpartum: Regulation by thyroid hormones - Varas, Silvia Mabel (2005)
The aim of this study was to examine, using semiquantitative reverse transcriptase-polymerase chain reaction (RT-PCR) the changes in mRNA expression of the two estrogen receptor (ER) subtypes, ERα and ERβ, prolactin receptor long and short form, and progesterone (Pg) receptor (PgR), in liver and mammary gland during gestation, early lactation, and weaning in both hyperthyroid (HT) and normal rats. Pregnancy increased long prolactin receptors (PRL-RL) and ERα mRNAs in liver and PRL-RL in mammary gland. Lactation decreased PRL-RL in liver and ERβ and PgR in mammary gland. HT decreased PRL-RL at the end of pregnancy (G21), ERα (in G21 and L1) in liver and PRL-RL in L1 as well as short prolactin receptors (PRL-RS) (G7, L1) and ERβ (G7, G14, L4) in mammary gland. In conclusion, our data indicated that 1 PRL-R1 and ERα expression levels are differentially regulated in the liver, and PgR and ERβ in mammary gland during pregnancy and lactation 2 ERβ is variably expressed depending on the state of thyroid hormones, however the ERα gene expression remained constant in mammary gland. 3 PRL-R1 mRNA expression is highly induced in the mammary gland during late pregnancy and abruptly declines on the first day of lactation for the HT rats.